Multimodal imaging of congenital pyriform fossa fistula in children - Zhai, Aiguo; Peng, Xuehua; Guo, Yu; Li, Jian; Shao, Jianbo (Frontiers in Pediatrics, 2023)
Objective Our aim was to explore the clinical value of multimodal imaging examinations in the diagnosis of congenital pyriform fossa fistula in children, so as to provide clues for the early diagnosis and treatment of congenital pyriform fossa fistula. Methods The clinical and imaging data of 55 children with pyriform fossa fistula diagnosed surgically in our hospital from 2015 to 2018 were analyzed retrospectively. All 55 patients underwent a CT scan. Of those patients, contrast enhancement CT was performed in 47 cases, MRI was performed in 2 cases, and barium esophagography was performed in 41 cases. Results Among the 55 cases, there were 24 male patients and 31 female patients. The age ranged from 11 months to 13 years old, and the median age was 3.8 years old. The lesions of 49 cases (89.1%) were located on the left side, and the imaging of CT showed soft tissue mass in the anterior cervical region blurred boundary. There was ipsilateral thyroid involvement in 50 cases (90.9%), trachea and/or carotid sheath extension in 43 cases (78.2%), abscess formation in 39 cases (70.9%), and pneumatosis in 25 cases (45.5%). The CT examination of 22 children after treatment showed a linear or tubular low-density shadow in the thyroid gland, gas accumulation in the anterior cervical region or thyroid, and residual contrast medium, partly. A total of 24 cases underwent barium esophagography during the acute phase, and 15 cases (62.5%) showed sinus formation from the pyriform fossa downward or punctate high-density shadow in the anterior cervical region. The 2 cases where MRI was performed showed abscess formation in one side of the neck and thyroid involvement. Conclusion Pyriform fossa fistula is most common in the left anterior cervical region, and it is closely related to the thyroid gland. The plain and enhanced-contrast CT scan can be used as the first choice during the infection stage. It helps to understand the location, extent, and structure of the surrounding tissue. The preliminary diagnosis of pyriform sinus fistula was according to the imaging features. It provided an important basis for clinical diagnosis and reduced the pain caused by repeated infection or surgical incision and drainage.